SOLID MEDICAL WASTE MANAGEMENT IN HOSPITALS: CONSTRAINTS, IMPACTS, AND OPTIMIZATION STRATEGIES - Ernawati, Siti Umi; Andarini, Sri; Hariyanti, Tita (Universitas Brawijaya, 2025)
Solid medical waste management remains a significant challenge in Indonesia. According to data from the 2022 Indonesian Health Profile , only 38.9% of hospitals and health centers in Indonesia adhere to established standards for medical waste management. The impact of not managing medical waste according to standards is the increased risk of health and environmental problems. The present research design is of a qualitative nature, employing a case study approach in a government hospital. The data collection methods included in-depth interviews, document analysis, and field observations. The purposive sampling technique was employed, focusing on selecting participants who deeply understand the subject matter under investigation. The sample comprised seven individuals/informants from the Government Hospital, the Health Office, and the recipient of waste treatment services. The data derived from these interviews, document analysis, and field observations were systematically analyzed until the point of saturation was reached. The analysis yielded eight themes: The management delayed enforcing green hospital policies; The management neglected organizational governance of solid medical waste management without any policy; Technical governance of solid medical waste management was perplexing: policy or opportunity?; Inadequate communication and coordination between management and units; Hospital visitors and third parties slowed down the solid medical waste management process; The impact of management delays: solid medical waste accumulated; Inefficiency due to missing all recycling opportunities for solid medical waste; and The strategies for optimizing solid medical waste management governance. It can be concluded that the management of solid medical waste in government-owned hospitals is not yet at the most effective state, and there are still wastes and constraints in its governance. To address these issues, a number of strategies have been implemented, including adjustments to medical waste management and educational initiatives targeting the hospital community.